STUDI PERSEPSI WAJIB PAJAK TERHADAP PELAYANAN SISTEM ONLINE PAJAK BUMI DAN BANGUNAN (STUDI KASUS PADA DINAS PENDAPATAN KOTA MALANG) - Rozanna, Zita Aprilia (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study aims to understand the influence of the the quality of service to ease technology and know the quality of service and ease the use of technology to paytax online against satisfaction taxpayers inrevenue regional government of Malang.The use writers three variables in this research that is the quality of services, ease the use of technology, and satisfaction taxpayers. The use writers research methodology partial least square using data primary .The result shows that the quality of services have had a positive impact significant directly against ease the use of technology, The quality of services have had a positive impact indirectly to satisfaction taxpayers through ease technology and ease technology significant positive directly against satisfaction taxpayers.Keywords: Service Quality, Pay Tax Online, Satisfaction Taxpayers